1994
DOI: 10.1093/schbul/20.2.287
|View full text |Cite
|
Sign up to set email alerts
|

Age at Onset in Subtypes of Schizophrenic Disorders

Abstract: Age at onset and sex differences in the age at onset were investigated in the schizophrenic subtypes of 200 patients. Significant differences in the age at onset were observed among these subtypes; the disorganized subtype demonstrated the earliest and the paranoid the latest onset. The mean age at onset of all female patients was significantly greater than that of the male. Specifically, in the paranoid subtype the onset for men occurred earlier than for women. Conversely, in the disorganized subtype the diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 31 publications
(36 reference statements)
2
33
1
1
Order By: Relevance
“…Women have been found to experience more paranoid symptoms (Beratis et al, 1994) and to be more likely to appear depressed than men (Morgan et al, 2008). The presence of affective symptoms is linked to more favourable outcomes (Lewine, 2004).…”
Section: Development Of Schizophrenia In Womenmentioning
confidence: 99%
“…Women have been found to experience more paranoid symptoms (Beratis et al, 1994) and to be more likely to appear depressed than men (Morgan et al, 2008). The presence of affective symptoms is linked to more favourable outcomes (Lewine, 2004).…”
Section: Development Of Schizophrenia In Womenmentioning
confidence: 99%
“…15 Siblings who are past this critical age might therefore no longer be at high risk for schizophrenia, which might reduce the likelihood of finding grey matter abnormalities in this group. Second, the risk for schizophrenia increases as genetic load increases.…”
Section: J Psychiatry Neurosci 2015;40(3)mentioning
confidence: 99%
“…To what extent DDC might influence these specific parameters should be scrutinized in future studies of suitable patient samples. Moreover, several studies have reported that the early onset in males was particularly evident in paranoid schizophrenia, [22][23][24] and paranoid symptoms have been specifically related to increased dopaminergic activity on the basis of amphetamine-induced psychosis. 25,26 It has been shown that amphetamine causes a reduction in DDC mRNA and 2-PE production.…”
Section: ‫ء‬mentioning
confidence: 99%